A NEXUS OF INTELLIGENCE ON THE READING ABILITY OF KINDERGARTEN STUDENTS - Epi Supriyani Siregar (FKIP Universitas Al Washliyah Medan, 2018)
Reading is a receptive written language skill. Reading skills are complex activities that involve a variety of skills. This study aims to determine the differences in reading skills of Kindergarten students Nurul Azizi Medan in the academic year 2005/2006 between those who have high intelligence and those with low intelligence. The sample of this study consisted of 20 children. The method used is a quasi-experimental 2x2 factorial design. The analysis technique used is the two-way analysis of variance (two-way ANOVA 2x2) with a level of α = 0.05 using the F-test, further testing using the Tuckey test. The result is that there is a difference in the reading ability of Kindergarten students between those who have high intelligence is better than those who have low intelligence at the level of confidence α = 0.05 with Fh = 13.42 > FT = 4.09, using the Tuckey test obtained Q count = 4.58 > Q table = 3.96. Overall, Kindergarten students who have high intelligence are better than those who have low intelligence.